2022
DOI: 10.1155/2022/9502749
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in the Prediction of Leg Numbness after Spinal Endoscopic Surgery: Evaluation and Development of a Nomogram

Abstract: Purpose. This study aims at constructing a clinical predictive model that predicted the risk factors for leg numbness after spinal endoscopic surgery. Methods. We collected the clinical data of patients, including general information, imaging parameters, and clinical score, from our hospital’s electronic database. Based on the postoperative leg numbness visual analog scale (LN-VAS), the clinical data were divided into the leg numbness group (≥25) and the improvement group (<25). All parameters were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[ 7 ] A retrospective study of 73 patients with LDH by Yi et al (2022) found that LN after spinal endoscopic surgery was associated with longer symptom duration, pelvic incidence, preoperative LBP VAS score, and LDH combined with LSS. [ 11 ] Additionally, a study by Tsujimoto et al (2023) on symptomatic postoperative lumbar epidural hematoma also found that compared to early removal of hematoma, delayed removal of hematoma can also improve LBP and LP but not LN. [ 18 ] Therefore, patients in the RLN group had a longer preoperative LN duration in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] A retrospective study of 73 patients with LDH by Yi et al (2022) found that LN after spinal endoscopic surgery was associated with longer symptom duration, pelvic incidence, preoperative LBP VAS score, and LDH combined with LSS. [ 11 ] Additionally, a study by Tsujimoto et al (2023) on symptomatic postoperative lumbar epidural hematoma also found that compared to early removal of hematoma, delayed removal of hematoma can also improve LBP and LP but not LN. [ 18 ] Therefore, patients in the RLN group had a longer preoperative LN duration in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] However, only a few studies have specifically investigated the potential risk factors of RLN after microdiscectomy in patients with LDH. [10,11] The association of clinical and radiological factors, such as sex, age, body mass index (BMI), current smoking, diabetes mellitus, duration of preoperative LN, preoperative LN NRS score, RLN at discharge, revision surgery, sagittal range of motion (SROM), intervertebral Modic change, disc Pfirrmann grade with RLN remains unclear.…”
Section: Introductionmentioning
confidence: 99%